Dosing Accuracy of Oral Extemporaneous Suspensions of Antibiotics: Measuring Procedures and Administration Devices - Inês Neves; Maria D. Auxtero (MDPI AG, 2021)
Extemporaneous suspensions are often marketed with several administration devices that can be freely used by patients/caregivers. The homogeneity of suspensions requires shaking before use. Hence, it is crucial to assess the precision of all devices and the users' awareness of the shaking procedure. This study was conducted at University Institute Egas Moniz with 40 pharmacy students who were asked to measure 2.5 and 5 mL of two extemporaneous azithromycin suspensions. Formulation A is marketed with a double-dosing spoon and oral syringe, whereas B includes a transparent dosing spoon. Both have a reconstitution cup. The user's preference for administration devices, the degree of compliance with the 'shake before use' instruction and the accuracy of the manipulation were assessed. The double-dosing spoon was the preferred device. The "shake before use" instruction was overlooked by most volunteers. The average measured volumes obtained with the double-dosing spoon were significantly different from the ones obtained with the oral syringe (p < 0.001) and significantly lower than the reference dose (p < 0.001). The oral syringe originates significantly higher values than the reference dose (p < 0.001). The dosing spoons values were significantly different from each other (p < 0.001). Liquid medicines containing several administration devices may be a challenge since they are nonequivalent.